Magnetic and structural properties of Zn doped MnV2O4 - Shahi P.; Shukla K.K.; Singh R.; Das A.; Ghosh A.K.; Nigam A.K.; Chatterjee S. (My University, 2025)
The magnetization, Neutron diffraction and X-ray diffraction of Zn doped MnV2O4 as a function of temperature have been measured. It has been observed, with increase of Zn the non-linear orientation of Mn spins with the V spins will decrease which effectively decrease the structural transition temperature more rapidly than Curie Temperature. © 2014 AIP Publishing LLC.